Grau de subestimação histopatológica por Core biopsy de lesões não-palpáveis da mama - Gonçalves, Aline Valadão Britto (2011)
Objective: The purpose of this study was to determinate the rate of underestimation of core biopsy (CB) of nonpalpable breast lesions, under image guidance, with validation at surgical excision histologic examination at Instituto Nacional de Câncer (INCA). Materials e methods: We retrospectively reviewed 352 CB that were submmited to surgery, from February 2000 to December 2005, and which histopathologic findings were at INCA database system. CB results were compared to surgical findings and underestimation rate was determined by dividing the number of lesions that proved to be carcinoma at surgical excision by the total number of high risk lesions and intracuctal carcinoma evaluated with excisional biopsy. Clinical, imaging, core biopsy and pathologic features were analyzed to identify factors that affect the rate of underestimation. Results: All patients were female, which mean age was 56,1 years old (26-86). Mass lesion was the most frequent finding (71,3%), being 69,9% less than 20mm, as well as BI-RADS® 4 (71,0%). The main guidance was stereotactic (57,1%), all using 14-gauge needles. The mean number of core samples was eight (4-22), being 99,7% at least five samples. The patients tolerated CB in 99,1% of cases, but bleeding occurred in 6,6%. The inconclusive CB findings occurred in 15,6%, (55/352). It was benign in 26,4%, high risk lesion in 12,8% and malignant in 45,2%. The segmentectomia was the more frequent surgery (70,2%), being benign in 26,7%, high risk in 18,2% and malign in 55,1%. There was agreement between CB and surgery in 82,1% (Kappa = 0,75). False-negative rate was 5,4% and the lesion was completely removed in 3,4%. Underestimation rate was 9,1%, and was associated with BI-RADS® 5 (p = 0,049), microcalcifications (p < 0,001) and stereotactic guidance (p = 0,002). All underestimated cases were less than 20 mm of diameter and there were at least five fragments. Underestimation rate of high risk lesions was 31,1% and there was no significant associations. Atypical ductal hyperplasia underestimation rate was 41,2% and there was not associations. Papillary lesions underestimation was 31,2% and was associated with stereotactic guidance (p = 0,036). Phyllodes tumor underestimation was 16,7% but it was not possible to make associations. There was one lobular neoplasia case that was concordant to surgery. Ductal carcinoma in situ underestimation was 41,9% and there was not significant associations. Conclusions: The core breast biopsy under image guidance is a reliable procedure but it remains the recommendation of surgical excision for high risk lesions detected at CB as well as it was not possible to assess clinical, imaging, core biopsy and pathologic features that could predict underestimation and avoid excision. Representative samples are much more important than number of fragments.